2012
DOI: 10.1017/aee.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Education and Teacher Education: Finding a Natural Habitat?

Abstract: Sustainability education competes for curricular space, both in schools and in teacher education. Opportunities and barriers for the inclusion of sustainability education in an Australian university primary teacher education program are examined in this article. The study focused on the roles, practices and perceptions of teacher educators in promoting sustainability education. Three focus groups were conducted with members of faculty staff from each of the K–6 Key Learning Areas to gather data, which were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 35 publications
(46 reference statements)
1
38
0
Order By: Relevance
“…However, for science teacher educators the main goals were "to promote meaningful learning of science concepts and to inspire students' interest in learning about science" [72] (p. 121). Buchanan [73] investigated sustainability education in Australian primary teacher education in a focus group study with teacher educators representing all the subjects in the curriculum of primary education. The analysis of the discussions in focus groups revealed that it was not easy to come to a common and unambiguous understanding of the concept of sustainability education.…”
Section: Sustainability In Teacher Educationmentioning
confidence: 99%
“…However, for science teacher educators the main goals were "to promote meaningful learning of science concepts and to inspire students' interest in learning about science" [72] (p. 121). Buchanan [73] investigated sustainability education in Australian primary teacher education in a focus group study with teacher educators representing all the subjects in the curriculum of primary education. The analysis of the discussions in focus groups revealed that it was not easy to come to a common and unambiguous understanding of the concept of sustainability education.…”
Section: Sustainability In Teacher Educationmentioning
confidence: 99%
“…We, like others (e.g., Buchanan, 2012;Mills & Tomas, 2013;Nolet, 2009;Summers et al, 2005), believe that teacher education programs must play a critical role in this endeavour. However, it is insufficient and perhaps even neglectful to simply tell ITES they have to embed this CCP (or any CCP, for that matter) across learning areas whilst assuming that somehow ITES will figure this out by themselves.…”
Section: The Role Of Initial Teacher Education and Higher Educationmentioning
confidence: 75%
“…Indeed, the literature is replete with evidence of the challenges for in-service teachers and ITES to respond to the calls for prioritizing and implementing sustainability education. A mounting body of literature points to both the limiting and enabling factors that have been encountered with efforts to deliver sustainability in the formal education system in schools (N. Evans, Whitehouse, & Gooch, 2012), in ITE programs (Buchanan, 2012;Mills & Tomas, 2013) and in higher education generally (Cotton, Warren, Maiboroda, & Bailey, 2007;Jones, Selby, & Sterling, 2010). While it is beyond the scope of this paper to review all of these barriers and enablers for the three sectors, a recent Australian study provides a helpful framework for understanding the barriers and enablers to implementing sustainability education (N. Evans et al, 2012).…”
Section: Pre-service Teachers and Teaching Sustainability: Barriers Amentioning
confidence: 99%
See 2 more Smart Citations